Perancangan Ulang Stasiun Cisauk Kabupaten Tangerang Dengan Pendekatan Teknologi - Rindra Mangkuluhur, Sri; Firmansyah, Rangga; Septony Siregar, Fernando (eProceedings of Art & Design, 2024)
Cisauk Station, located in Tangerang Regency, Banten, faces various challenges related to the lack of supporting facilities and the optimal implementation of information technology. To address this, this study redesigns the interior of Cisauk Station with the concept of a "Smart Urban Transit Hub" to support the transformation of BSD City into a smart city and align with the vision of PT Kereta Api Indonesia (PT KAI) in realizing digital transformation in the transportation sector. Data collection was conducted through field studies, literature reviews, comparative studies, and precedent studies to produce optimal design solutions. The "Smart Flow Station" concept was applied to create an environment that is efficient, easy, and comfortable for users. The interior design focused on the use of technology, such as real-time information systems and digital ticket payments, to enhance mobility efficiency and user experience. The redesign is expected to make Cisauk Station a model for future transit hubs, combining technological advancements with the needs of the urban community, while also strengthening BSD City's role as a center of innovation and technology. Keywords: railway stations, transportation, technology, innovation